2011
DOI: 10.1039/c0cp02694h
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-classical trajectory study of the dynamics of the Cl + CH4→ HCl + CH3 reaction

Abstract: We present an on-the-fly classical trajectory study of the Cl + CH4  HCl + CH3 reaction using a specific reaction parameter (SRP) AM1 Hamiltonian that was previously optimized for the Cl +

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 57 publications
0
35
1
Order By: Relevance
“…(Note that a recent study 28 reported a classical barrier height of 2385 cm −1 obtained at CCSD(T)/CBS//CCSD(T)/aug-cc-pVTZ, which value is slightly smaller than our more rigorous CCSD(T)/CBS value of 2440 cm −1 and much smaller than our benchmark value of 2670 cm −1 . The difference in the CBS value is due to the fact that Ref.…”
Section: The CL + Ch 4 → Hcl + Ch 3 Reactioncontrasting
confidence: 61%
See 1 more Smart Citation
“…(Note that a recent study 28 reported a classical barrier height of 2385 cm −1 obtained at CCSD(T)/CBS//CCSD(T)/aug-cc-pVTZ, which value is slightly smaller than our more rigorous CCSD(T)/CBS value of 2440 cm −1 and much smaller than our benchmark value of 2670 cm −1 . The difference in the CBS value is due to the fact that Ref.…”
Section: The CL + Ch 4 → Hcl + Ch 3 Reactioncontrasting
confidence: 61%
“…Also in that year, Troya and Weiss 12 reported a specific reaction parameter (SRP) semi-empirical Hamiltonian (SRP-MSINDO) for the Cl + CH 4 reaction allowing efficient on-the-fly computation of the PES. In 2011 Greaves et al 28 showed that another semi-empirical Hamiltonian (SRP-AM1), which was previously optimized for the Cl + ethane reaction, can be used for the title reaction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Troya and coworkers used a full-dimensional semi-empirical PES to perform quasi-classicaltrajectory (QCT) calculations. [38][39] The first global pre-calculated ab initio PES used in QCT calculations was reported by Castillo et al 40 Their approach used QCISD(T)/aug-cc-pVTZ//QCISD/cc-pVTZ calculations to determine the energies of the separated reactants and products and those of the preand post-reaction complexes. The other regions of the PES were calculated using the interpolation algorithms of Collins and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Fully dimensional on-the-fly classical dynamics calculations were carried out for the CH4 + Cl reaction using a semi-empirical model Hamiltonian by Troya et al 38,45 and using the Hartree-Fock /6-31G level of theory by Rudić et al 46 A similar approach was adopted by Greaves et al who investigated the transferability of model Hamiltonians between related reactions. 39 The purpose of the current study is to test the EVB description of a PES generated from high level ab initio electronic structure calculations. The EVB fit to obtain a global PES requires fewer ab initio points than the alternative PES fitting methods described above.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the bonds that do not break retain their initial excitation and are, to a first approximation, simply spectators in the reaction. 2,3,[8][9][10] This well-characterized behavior of the methane isotopologues, as well as the importance of reactions of methane with Cl in the upper atmosphere, 11 have motivated a large set of experimental 1-5, 8-10, 12-20 and theoretical [21][22][23][24][25][26][27] studies, placing reactions of methane among the most carefully studied of any polyatomic molecule. Against this backdrop, we investigate experimentally the energetics of the reaction of CH 3 D with Cl to make a careful comparison with theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%